2023
DOI: 10.3390/ijms24043735
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Inflammation, and Microbiota in Alcoholic Liver Disease

Abstract: Alcoholic liver disease (ALD) is a consequence of excessive alcohol use. According to many studies, alcohol represents a significant socioeconomic and health risk factor in today’s population. According to data from the World Health Organization, there are about 75 million people who have alcohol disorders, and it is well known that its use leads to serious health problems. ALD is a multimodality spectrum that includes alcoholic fatty liver disease (AFL) and alcoholic steatohepatitis (ASH), consequently leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 95 publications
0
19
1
4
Order By: Relevance
“…This suggests that drinking history itself may represent broader influences. Firstly, alcohol consumption can exacerbate liver inflammation and fibrosis, [20][21][22][23][24] Inflammation leads to liver tissue damage and destruction, affecting normal liver function. Inflammatory responses also activate the release of inflammatory mediators, further increasing vascular permeability and impairing lymphatic circulation, thereby promoting pleural effusion formation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that drinking history itself may represent broader influences. Firstly, alcohol consumption can exacerbate liver inflammation and fibrosis, [20][21][22][23][24] Inflammation leads to liver tissue damage and destruction, affecting normal liver function. Inflammatory responses also activate the release of inflammatory mediators, further increasing vascular permeability and impairing lymphatic circulation, thereby promoting pleural effusion formation.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term heavy drinking can lead to inflammation and apoptosis ( 53 , 54 ). Pro-BDNF and BDNF may produce opposite biological functions by signaling through p75NTR and TrkB, respectively ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the likelihood of developing ALD increases with increased alcohol consumption, extensive individual variability exists ( 7 ) indicating that while excessive alcohol consumption is necessary for the development of ALD, it alone is not sufficient in inducing ALD. Several experiment studies in animal models and human ( 11 , 12 ) have demonstrated that inflammation is required for alcohol-induced liver cell injury and clinically relevant ALD. One of the primary sources of systemic and hepatic inflammation in AUD seems to be alcohol-induced gut microbiota dysbiosis and disruption of intestinal barrier (gut leakiness to endotoxins and other proinflammatory products of gut microbiota) ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%